The financing of environmental oversight: a task for everyone or only some? - López Montreuil, Uber (2019)
The Constitutional Court has recently validated the payment of regulatory fees to OEFA. However, a series of substantial considerations were not taken into account in this Court’s analysis to solve the controversy surrounding such payments. Among them, the debate on its legal nature and the activity it funds. On this basis, this article analyses the formal and material validity of the aforementioned regulatory fees taking into account their legal nature. It examines, as well, the impact of the recent ruling on the Peruvian legal framework and the possibility of questioning this decision in the available jurisdictional arenas.